Penerapan Metode Drill (Latihan) dalam Mempengaruhi Hasil Belajar Siswa Pada Mata Pelajaran IPS Terpadu Kelas VIII Raudlatul Wathoni - Izzudin, Ahmad (Lembaga Pendidikan Al-Gafari, 2025)
The Drill method is a teaching method to instill and maintain good habits and to acquire dexterity, accuracy and skills. The goal to be achieved is to find out whether the Drill method has an effect on the learning effectiveness of Class VIII students of MTs. Raudlatu Wathoni. In this study, the population was Class VIII MTs. Raudlatu Wathoni, while the sample used was class VIII students of MTs. Raudlatu Wathoni. Data collection techniques were carried out by pre-test and post-test. This type of research is experimental. Based on the results of the study and data collection obtained from the Control group (student learning outcome data using the Drill learning method approach (exercise) obtained the highest score for students in the control group was 80 and the lowest score was 20. While the highest score for students in the experimental group was 90 and the lowest score was 25. From the calculation results obtained the average (mean) of the experimental group for student learning effectiveness was 63.83 with a standard deviation (SD) for the control group was 16.97 while for student learning effectiveness obtained the average (mean) was 53.84 with a standard deviation (SD) of 16.03. From the results of the test that has been carried out using the t-test formula obtained tcount tcount = 2.85> ttable = 1.994 at a significance level of 5%. By comparing the tcount price with ttable from the test results, it is stated that tcount> ttable or tcount 2.85> ttable 1.994. Thus, there is a positive and significant influence of the learning method Drills (exercises) have an effect on the learning outcomes of social studies of class VIII students of MTs. Raudlatu Wathoni.